2013
DOI: 10.1093/mnras/sts561
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the transverse structure of the relativistic jets of active galactic nuclei

Abstract: This paper describes a method of fitting total intensity and polarization profiles in VLBI images of astrophysical jets to profiles predicted by a theoretical model. As an example, the method is used to fit profiles of the jet in the Active Galactic Nucleus Mrk 501 with profiles predicted by a model in which a cylindrical jet of synchrotron plasma is threaded by a magnetic field with helical and disordered components. This fitting yields model Stokes Q profiles that agree with the observed profiles to within t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 30 publications
1
41
1
Order By: Relevance
“…This was initially interpreted as evidence for transverse shocks in their jets, which enhanced the magnetic field in the plane of compression; more recently, it has been suggested that these orthogonal fields may represent the central part of a helical or toroidal field component. This latter idea is supported by the observation of spine-sheath polarization structures [2], [3] (see Fig. 1) and transverse Faraday-rotation gradients [4] - [7] (see below) in a number of BL Lac objects.…”
Section: Bl-lac Objectsmentioning
confidence: 64%
“…This was initially interpreted as evidence for transverse shocks in their jets, which enhanced the magnetic field in the plane of compression; more recently, it has been suggested that these orthogonal fields may represent the central part of a helical or toroidal field component. This latter idea is supported by the observation of spine-sheath polarization structures [2], [3] (see Fig. 1) and transverse Faraday-rotation gradients [4] - [7] (see below) in a number of BL Lac objects.…”
Section: Bl-lac Objectsmentioning
confidence: 64%
“…This theoretical picture is supported by indirect observational evidence (AGN warm absorbers [4], Faraday RM gradients across astrophysical jets [5][6][7], polarization measurements [8], XRB Hardness-Intensity q-diagrams [9], GRB exponential afterglow decay [10], etc. ), and by state-of-the-art MHD simulations [11].…”
Section: Introductionmentioning
confidence: 78%
“…For example, Donald Lynden-Bell looked at published intrinsic Faraday RM maps for the centres of galaxies seen at inclination angles of less than 60 • and found evidence that their central magnetic fields are preferentially oriented along the angular velocity vector of the galaxy (obtained from the direction of the galactic spirals), in accordance with the Cosmic Battery [25]. Other observations that require further investigation are asymmetric profiles of total intensity and polarization across the jets [26], magnetic field orientation changing from longitudinal to transverse [8], linear to circular polarization conversion [27], RM maps from background sources around the jet [28,29], etc. The latter, in particular, are very significant since, according to the Cosmic Battery and observations reported in the present work, the large scale magnetic field that threads the kpc-scale jet consists of the return part of the magnetic field that threads the central black hole and possibly forms an electron-positron barely observable jet spine [30].…”
Section: Future Researchmentioning
confidence: 99%
“…Magnetohydrodynamical (MHD) simulations have also been used to produce jet simulations; these treat the magnetic field as dynamically important, e.g., [26][27][28]. However, the MHD approach requires extremely high resolutions to represent the disordered field that observations lead us to expect [29], resulting in a prohibitively large simulational run-time if MHD code were to be used in this work.…”
Section: Numerical Simulationsmentioning
confidence: 99%